Network analysis of the Viking Age in Ireland as portrayed in Cogadh Gaedhel re Gallaibh - Yose, Joseph; Kenna, Ralph; MacCarron, Máirín; MacCarron, Pádraig (Royal Society open science, 2018)
Cogadh Gaedhel re Gallaibh (‘The War of the Gaedhil with the Gaill’) is a medieval Irish text, telling how an army under the leadership of Brian Boru challenged Viking invaders and their allies in Ireland, culminating with the Battle of Clontarf in 1014. Brian’s victory is widely remembered for breaking Viking power in Ireland, although much modern scholarship disputes traditional perceptions. Instead of an international conflict between Irish and Viking, interpretations based on revisionist scholarship consider it a domestic feud or civil war. Counter-revisionists challenge this view and a long-standing and lively debate continues. Here, we introduce quantitative measures to the discussions. We present statistical analyses of network data embedded in the text to position its sets of interactions on a spectrum from the domestic to the international. This delivers a picture that lies between antipodal traditional and revisionist extremes; hostilities recorded in the text are mostly between Irish and Viking—but internal conflict forms a significant proportion of the negative interactions too.